Industrial production of bleach and quality control (Research, Society and Development, 2022)
Bleach is a widely used sanitizer due to its high disinfection and bleaching power. The production process must be monitored by quality control from the receipt of raw materials to the finished product packaged. The objective of this review article is about the processing and production of bleach, with the controls carried out during the production process: physical-chemical control, packaging composition, applications and risks. The research was carried out by searching for information on the internet about published scientific articles, covering topics such as the concentration of active chlorine, the efficiency of sanitization for hortifruti, the efficiency against the dengue mosquito larvae and information on care during handling, avoiding domestic accidents. In view of the information researched, it was concluded that bleach is very efficient in sanitizing and sanitizing as long as it is in the ideal concentration and receives all the necessary controls during the production process.